2018
DOI: 10.1186/s12891-018-1972-3
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in total shoulder arthroplasty and reverse shoulder arthroplasty: a systematic review and meta-analysis

Abstract: BackgroundThe effects of tranexamic acid (TXA) in the setting of shoulder arthroplasty are unclear. The objective of this study was to examine the effects of TXA in reducing the need for blood transfusions and blood loss in patients undergoing primary total shoulder arthroplasty (TSA) and reverse total shoulder arthroplasty (RTSA).MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) and retrospective cohort studies (RCS) that compared outcomes of patients who did and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 40 publications
(91 reference statements)
4
42
1
2
Order By: Relevance
“…It is possible that the decrease in postoperative blood transfusion observed in this study is related to the growing popularity of using tranexamic acid during TSA. Indeed, a meta-analysis by Kuo et al 25 showed a risk ratio of 0.34 (95% confidence interval: 0.14-0.79) for transfusion after TSA when tranexamic acid was used.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the decrease in postoperative blood transfusion observed in this study is related to the growing popularity of using tranexamic acid during TSA. Indeed, a meta-analysis by Kuo et al 25 showed a risk ratio of 0.34 (95% confidence interval: 0.14-0.79) for transfusion after TSA when tranexamic acid was used.…”
Section: Discussionmentioning
confidence: 99%
“…Improved perioperative care is likely contributing to these, such as better wound closure techniques, improved wound dressing, the utilization of tranexamic acid, and other blood preservation techniques. 29-31 As the LOS for all procedures also decreased, this raises the question whether the complication burden, particularly for those complications that present several days after joint arthroplasty, was merely shifted to intermediate care facilities such as skilled nursing facilities or acute rehab facilities to which joint arthroplasty patients were discharged. 20,25,28 In an era of intensified focus to shift joint arthroplasty to an outpatient setting, this issue deserves further study because it potentially represents an important patient safety issue.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been developed to control bleeding during spinal surgery and mainly include minimal invasion procedures, patient positioning, deliberate hypotension, intraabdominal pressure control, infiltration of paraspinal tissues using vasoconstrictors, and pharmacological agents to enhance coagulation [10,[22][23][24][25]. TXA is known as an antifibrinolytic agent and acts through blocking the interaction of plasminogen and plasmin by competing with the lysine residues on the surface of fibrin to inhibit the fibrinolysis, resulting in clot stabilization [26][27][28][29]. Our study suggests that preoperative and intraoperative intravenous infusion of TXA can substantially reduce intraoperative blood loss and time to ambulation but shows no obvious impact on hospital stay after surgery, postoperative drainage, time for drainage removal, or postoperative Hb.…”
Section: Discussionmentioning
confidence: 99%